Efficacy and safety of generic and original pioglitazone in type 2 diabetes mellitus: A multicenter, a double-blinded, randomized-controlled study - Petch Rawdaree (2018)
Objective: To compare the efficacy and safety of generic (Utmos®) and original (Actos®) 30 mg Pioglitazone tablets. Study design: A multicenter, parallel randomized, double-blinded, controlled study. Material and Method: Type 2 diabetic patients, with glycosylated hemoglobin (HbA1c) ≥ 7.0%, who received Metformin not less than 1,000 mg/day over three months were recruited. Patients were randomized to receive either generic or original Pioglitazone 30 mg/day for 24 weeks. Results: Eighty-five patients were enrolled, forty-four patients received generic Pioglitazone and forty-one received original Pioglitazone. There were no significant differences in baseline characteristics between generic and original Pioglitazone group. There were significantly reduced HbA1c, fasting plasma glucose (FPG) and significantly increased HDL-cholesterol from baseline (p < 0.0001) without statistically differences between the two groups. Headache and edema were found in both groups at comparable rates (p > 0.05). Conclusion: Generic Pioglitazone (Utmos®) is effective in controlling blood glucose and has similar effects on lipid profile as the original one. Both generic (Utmos®) and original (Actos®) 30 mg Pioglitazone tablets were not different in the efficacy and safety profiles.